2008
DOI: 10.1021/es8008166
|View full text |Cite
|
Sign up to set email alerts
|

Apportionment of Primary and Secondary Organic Aerosols in Southern California during the 2005 Study of Organic Aerosols in Riverside (SOAR-1)

Abstract: Ambient sampling was conducted in Riverside, California during the 2005 Study of Organic Aerosols in Riverside to characterize the composition and sources of organic aerosol using a variety of state-of-the-art instrumentation and source apportionment techniques. The secondary organic aerosol (SOA) mass is estimated by elemental carbon and carbon monoxide tracer methods, water soluble organic carbon content, chemical mass balance of organic molecular markers, and positive matrix factorization of high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
280
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(306 citation statements)
references
References 57 publications
(127 reference statements)
22
280
3
Order By: Relevance
“…[27] From Figure 5d, if total OOA is taken as a surrogate for SOA, and the sum of HOA, CIOA, and LOA is taken as a surrogate for POA, then it can be concluded that SOA is dominant at the Pasadena ground site, which is consistent with earlier findings in Riverside, CA [Docherty et al, 2008].…”
Section: Source Apportionment Of Organic Aerosol Mass By Positive Matsupporting
confidence: 82%
“…[27] From Figure 5d, if total OOA is taken as a surrogate for SOA, and the sum of HOA, CIOA, and LOA is taken as a surrogate for POA, then it can be concluded that SOA is dominant at the Pasadena ground site, which is consistent with earlier findings in Riverside, CA [Docherty et al, 2008].…”
Section: Source Apportionment Of Organic Aerosol Mass By Positive Matsupporting
confidence: 82%
“…We applied the different methods for ON and OS estimation to ambient HR-AMS data acquired in Riverside, CA during the SOAR-1 campaign (30). OA was dominated by SOA (30), and the combination of high NO x and VOC concentrations should result in significant ON production. A comparison between the AMS PM 1 nitrate and ion chromatography (IC) PM 2.5 nitrate reveals agreement within the errors, which confirms that the majority of the AMS nitrate is inorganic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions from the SOM model were compared to measurements made by the aerosol mass spectrometer (AMS) during the Study of Organic Aerosols at Riverside (SOAR) in the summer of 2005 (Docherty et al, 2011(Docherty et al, , 2008. Over the 2-week simulation, the SOM model underpredicted total OA by 40 % at this location.…”
Section: Soa Concentrations and Precursor-resolved Compositionmentioning
confidence: 99%